Upaya Pemanfaatan Perpustakaan Sekolah dalam Meningkatkan Minat Baca Siswa di Sekolah Dasar Negeri Durian Kecamatan Janapria Kabupaten Lombok Tengah - Sahlan; Lalu Surya Jagat (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2025)
This study aims to examine the utilization of the school library in enhancing students’ reading interest at SDN Durian, Janapria District, Central Lombok Regency. This research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews with the principal, teachers, librarian, and students, as well as documentation of literacy activities. The findings revealed that the library plays a strategic role as a learning resource center and as an essential facility to foster a reading culture among students. The use of the library was proven to increase students’ learning motivation, independence, and academic achievement. However, several challenges were identified, including limited relevant book collections, a relatively small reading space, and simple library management. To address these issues, the school implemented a Scheduled Literacy Program held three times a week before lessons begin, supported by the principal, teachers, and librarian. This strategy effectively encourages students to develop a consistent reading habit. The impact of library utilization can be seen in students’ improved reading interest, broader knowledge, and better academic performance. Therefore, the school library plays an important role in improving the quality of education in primary schools through the strengthening of sustainable literacy culture.